Tidal Flood Mitigation Model Using the Life Cycle Approach (LCA) in Coastal Areas of Pekalongan City - Madusari, Benny Diah; Fitri, Amalia; Gunawan, Muhammad Ali; Mardiana, Tri Yusufi (KnE Social Sciences, 2024)
The government (both central and regional) has addressed the issue of tidal flooding in Pekalongan City through various means. However, tidal floods will continue to pose a threat to Pekalongan City in the future. It is necessary to integrate policy programs and research approaches that adhere to the principles of sustainable development (ecological justice). One of the popular models today is the Life Cycle Approach (LCA). This study aims to 1) develop a tidal flood mitigation model in Pekalongan City using a Life Cycle Approach (LCA), 2) Analyze the advantages and disadvantages of applying a tidal flood mitigation model with a life cycle approach in the coastal area of Pekalongan City. This research is a development research carried out using a Participative Action Research (PRA) approach. Data collection techniques involve triangulation and analyzed using mixed methods. The results of this study indicate that: 1) the tidal flood mitigation model in Pekalongan City with a life cycle approach meets validation standards/criteria, 2) advantages: oriented to long-term solutions, more effective in overcoming tidal flood problems, can reduce maintenance costs, encourage involvement community, can improve environmental quality. Disadvantages of LCA: requires more time and cost, lack of flexibility, difficult decision-making, inability to guarantee project success, and lack of community participation, 3) Solutions to overcome weaknesses or disadvantages in implementing a tidal flood mitigation model with a life cycle approach in the coastal area of Pekalongan City, namely: a) speeding up the planning process, b) enhancing flexibility, c) improving transparency of decision-making, d) conducting simulations and trials, and e) increasing public participation. Keywords: mitigation model, tidal flooding, life cycle approach (LCA)